2004
DOI: 10.1128/aem.70.6.3512-3520.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Airborne Conidia of Fusarium circinatum , the Causal Agent of Pine Pitch Canker, from Two California Sites by Using a Real-Time PCR Approach Combined with a Simple Spore Trapping Method

Abstract: Pinus radiata (Monterey pine), a tree native to coastal California and Mexico, is widely planted worldwide for timber production. A major threat to Monterey pine plantations is the fungal disease pine pitch canker, caused by Fusarium circinatum (Hypocreales). We present a novel trapping approach using filter paper in combination with a rapid molecular method to detect the presence of inoculum in the air. The assay is also useful for diagnosing the presence of the pathogen on plants. The test is based on the F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
193
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(198 citation statements)
references
References 22 publications
2
193
1
2
Order By: Relevance
“…A possible explanation of this incongruence may be related to the contrasting spore trapping mechanisms used in the two studies. The spore traps used here sample the particles occurring directly in the air by impaction on the adhesive surface, while the passive spore traps used by Garbelotto et al [28] and in other research [18,39] sample the spores passively deposited on a filter paper. Passive deposition may be supported by rainfall, as the rain drops trap the air inoculum and deliver it onto the surface of the filter paper.…”
Section: Effect Of the Meteorological Conditionsmentioning
confidence: 99%
“…A possible explanation of this incongruence may be related to the contrasting spore trapping mechanisms used in the two studies. The spore traps used here sample the particles occurring directly in the air by impaction on the adhesive surface, while the passive spore traps used by Garbelotto et al [28] and in other research [18,39] sample the spores passively deposited on a filter paper. Passive deposition may be supported by rainfall, as the rain drops trap the air inoculum and deliver it onto the surface of the filter paper.…”
Section: Effect Of the Meteorological Conditionsmentioning
confidence: 99%
“…The incidence and spatial distribution of canker disease in oak trees has been attributed to the need for synchronicity of pathogen activity and seasonal host development (Dodd et al, 2008). The peak of sporulation by Phytophtora ramorum and Fusarium circinatum, the casual agents of sudden oak death canker disease and pine pitch canker, respectively, is when the climate is cool and humid (Schweigkofler et al, 2004;Dodd et al, 2008). Dodd et al (2008) demonstrated that the development of sudden oak death canker disease required coincidence of pathogen sporulation and activity of the host cambial tissue, and they found a strong correlation between date of largest lesion size and timing of spring bud burst.…”
Section: Developmental Stage Of the Hostmentioning
confidence: 99%
“…These results were obtained by assessing 30-50 asymptomatic seedlings on different occasions, over a one-year period from various nursery beds. The standard molecular identification method developed by Schweigkofler et al (2004) Using the information generated by Crous (2005), and the current establishment costs (pitting, planting and blanking), Mitchell et al (2009) calculated this loss to be R602 ha í1 for the saw timber industry, and R896 ha í1 for the pulpwood industry (Table 1). Extrapolated over South Africa, where approximately 15 000 ha are planted annually to P. patula (DAFF 2008), the impact of F. circinatum on tree survival costs the local forest industry in excess of R11 million per year (Mitchell et al 2009).…”
Section: Economic Impactmentioning
confidence: 99%